Genomic comparison between staphylococcus aureus isolates from patients with bacteraemia and infective endocarditis from public hospitals in Gauteng - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2025)
Dissertation (MSc (Medical Microbiology))--University of Pretoria, 2024.